PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GOOGLE SITES PADA MATA KULIAH DESAIN PESAN - Takdir, Muhammad; N, Zulkifli; Ferdiansyah, Handy (Academy of Education Journal, 2023)
This development research aims to (1) develop web-based learning media google sites, (2) to find out the validity, (3) and practicality of google sites web learning media in the message design course of the digital business study program of Muhammadiyah Sidenreng Rappang University. This research is a development research (Research and Development) with reference to the ADDIE development model. The subject of this study is one material expert, one media expert, course lecturer, and thirty students. The methods used in data collection are interviews, questionnaires, and test. The results of research and development: (1) This development research process is carried out in several stages, namely: Analysis, Design, Development, and Implementation. The analysis stage includes needs analysis studies, student characteristics analysis and Competency Analysis. The design stage includes the manufacture of learning tools, material expert instrument validators and media experts as well as lecturer and student questionnaires. The development stage includes the creation of multimedia learning products, validation of material experts and validation of media experts. The implementation stage is carried out in two cycles, namely individual trials and small group product trials, (2) the results of data analysis of learning media validation are in the very valid category, obtained from the assessment of material experts and media experts., (3) the results of the assessment of individual trial respondents, small group trials and lecturers' responses to web-based learning media google sites are declared very practical. Thus, learning media is valid, and practically used as a web-based learning media for google sites message design.